An efficient design method for LED surface sources in three-dimensional rotational geometry using projected angle difference An efficient design method for LED surface sources. (May 2019) - Li, X; Ge, P; Wang, H
An efficient method is proposed for the design of prescribed rotational illumination on the far or near field using the edge-ray principle. By this method, the prescribed illuminance on the prescribed location can be determined by projected angle difference in a two-dimensional design process for LED extended sources. Profiles of the lens with two initial curves on the centre can be calculated based on the relationship between the illuminance and the projected angle difference. The initial optical systems we calculated are close to the prescribed illumination despite the influence of skew rays. More importantly, a prescribed illumination on the near field can be achieved accurately and quickly by using this method, which is better than the usual luminous intensity distribution design methods for LED extended sources.